A new method to reduce false positive results in breast MRI by evaluation of multiple spectral regions in proton MR-spectroscopy. Issue 92 (July 2017) - Clauser, Paola; Marcon, Magda; Dietzel, Matthias; Baltzer, Pascal A.T.
Highlights: Choline showed a moderate performance as single diagnostic criterion for diagnosis of breast cancer. The water-to-fat ratio can be used to predict whether malignant lesions are Cho positive or not. Assessment of olefinic acids contributes independent diagnostic information. Combination of spectroscopic parameters showed a potential to substantially reduce false positive findings in benign breast lesions. Abstract: Objectives: To investigate whether the evaluation of multiple spectral regions can increase the diagnostic performance of 1 H-MRS of the breast and reduce false positive findings. Methods: 93 patients (mean age 56 years, range 23–79) undergoing breast MRI for routine clinical indications on a 1.5 T scanner were eligible for this IRB-approved prospective study. Suspicious enhancing lesions ≥8 mm underwent single-voxel point-resolved 1 H-MRS (PRESS, TR = 2000 ms, TE = 272 ms). Histology showed 69 malignant and 24 benign lesions. The Signal-to-Noise ratio of choline, olefinic acids and the water-to-methylene ratio were measured. The area under the ROC-curve (AUC) was used to evaluate single measurements. Combined diagnostic accuracy was explored using a 10-fold cross-validated Chi-squared automatic interaction detection (CHAID) analysis. Inter-reader agreement was evaluated in a subset of patients. Results: A significant AUC for differentiation between benign and malignant lesions was identified for choline (0.733, P = 0.001), olefinic acids (0.769, P = 0.0001) and water-to-methylene ratio (0.704, P = 0.003). All three variables were included in a classification algorithm using CHAID methodology. Using this classification, 70.8% (17/24) false positive diagnoses in benign lesions would have been avoided. Inter-reader agreement was almost perfect. Conclusions: The combined evaluation of multiple spectral regions can increase the diagnostic performance of 1 H-MRS and potentially reduce false positive findings.